An Assessment of How Engineering Students Partially Understand Derivatives through Six Cognitive Tasks - Sotomayor Cano , Sugey (2025)
This article reports on the findings attained from a questionnaire to assess learning difficulties encountered by engineering students regarding concepts about derivatives. The questionnaire was distributed to eleven students enrolled in the industrial, civil, and automation engineering programs. Analysis of the responses utilized theoretical and methodological concepts from the Ontosemiotic Approach (OSA) to Mathematical Knowledge and Instruction. Based on the results, 55% of students demonstrated  comprehension of derivatives as a rate of change and preferred the algebraic representation. Final recommendations are provided regarding tasks that should be integrated into calculus courses to strengthen the training of engineering students.